The dietary phytochemical index and its relation to polycystic ovary syndrome: a case-control study - Yasong Chi; Ruiqin Yue; Yanru Lv; Haiyan Li; Wei Liao (BMC, 2024)
Abstract Background Polycystic ovary syndrome (PCOS), a hormonal disorder affecting women of reproductive age, can be significantly impacted by diet. This study explores the relationship between a diet rich in phytochemicals, measured by the Dietary Phytochemical Index (DPI), and PCOS, along with associated health markers. Methods A case-control study design was implemented with 480 individuals diagnosed with PCOS based on the Rotterdam criteria, paired with 480 controls matched in terms of age and BMI. The evaluation encompassed dietary intake, anthropometric measurements, and hormonal/metabolic markers. Additionally, the DPI score was determined based on the consumption of phytochemical-rich foods. The study also examined PCOS-related complications like acne and irregular menstrual cycles, as well as mental health using the Beck Depression Inventory (BDI-II) scores. Results Women with PCOS had significantly lower DPI scores (32.42 vs 43.87, p < 0.001) compared to the control group, indicating a less phytochemical-rich diet. The DPI scores coincided with higher levels of hormones typically associated with PCOS, including Luteinizing Hormone (LH), Dehydroepiandrosterone Sulfate (DHEA-S), and testosterone. Additionally, these scores were associated with markers of metabolic dysfunction such as C-reactive Protein (CRP), Fasting Blood Sugar (FBS), and Homeostatic Model Assessment for Insulin Resistance (HOMA-IR), while positively correlating with Sex Hormone-Binding Globulin (SHBG) (all p < 0.050).). Higher DPI scores were associated with a significantly reduced risk of PCOS (OR: 0.13, 95% CI: 0.08, 0.23, P for trend: 0.001) and its complications, including acne and irregular menstrual cycles. Interestingly, a positive association emerged, suggesting better mental health (lower BDI-II scores) with higher DPI scores. Conclusions In conclusion, this study indicates that lower DPI scores are associated with a higher incidence and severity of PCOS, suggesting that a phytochemical-rich diet could potentially benefit the management of PCOS by enhancing hormonal profiles, metabolic health, and mental well-being in women.